Investigation of the Etiology of Molar Incisor Hypomineralization in Children Residing in Konya Province and Surrounding Areas, Türkiye - Aslı Seloğlu; Firdevs Kahvecioğlu (Children)
Background: According to the literature, hypomineralization of molars and incisors is a multifactorial condition that depends on both genetic and environmental factors. This study aims to diagnose Molar Incisor Hypomineralization (MIH) cases with a new index that better defines the defect and to contribute to the literature by identifying possible etiological factors. Methods: This research was conducted with children aged 8–11 years old and their parents from Konya province and surrounding provinces. While children who were diagnosed with MIH as a result of the examination constituted the study group, children with no findings of MIH during intraoral examination were included in the control group. Between February and October 2020, 104 patients for the study group and 104 patients for the control group were reached, and a survey was administered to a total of 208 parents. Results: Asthma, pneumonia, lower respiratory tract infections, diarrhea, a fever, and febrile convulsions between the ages of 0–4 have been found to be related to MIH (p < 0.05). Conclusions: The association between medical diseases in children and enamel defect formation draws attention to the importance of pediatricians in the early diagnosis of MIH cases. Pediatricians can be very helpful in informing parents of children with health problems about possible dental defects and referring them to a pediatric dentist.